Mild Cognitive Impairment Patients Have Higher Regulatory T-Cell Proportions Compared With Alzheimer's Disease-Related Dementia Patients - Fu, Jiping; Duan, Jinhai; Mo, Jianwei; Xiao, Hao; Huang, Yuedong; Chen, Weiping; Xiang, Shaotong; Yang, Fan; Chen, Yongjun; Xu, Shuwen (Frontiers in Aging Neuroscience, 2021)
Objectives: The role of neuroinflammation in the pathogenesis of Alzheimer’s disease (AD) has attracted much attention recently. Regulatory T cells (Tregs) play an important role in modulating inflammation. We aimed to explore the Tregs-related immunosuppression status at different stages of AD. Methods: 30 healthy control (HC) subjects, 26 mild cognitive impairment (MCI) patients, 30 mild probable AD dementia patients and 28 moderate-to-severe probable AD dementia patients underwent detailed clinical history taking, structural magnetic resonance imaging scanning and neuropsychological assessment. Peripheral blood samples were taken to measure the percentage of CD4+CD25+CD127low/- Tregs by flow cytometry and the levels of interleukin (IL10), interleukin (IL35) and transforming growth factor β (TGF-β) by ELISA. Results: The percentage of Tregs in the blood of MCI patients was the highest (9.24%), there was a significant difference between MCI patients and probable AD dementia patients. The level of TGF-β in MCI patients (47.02ng/ml) was significantly increased compared with AD dementia patients. There were positive correlations between Tregs percentage, IL35 and MMSE scores in MCI and probable AD dementia patients. Conclusions: MCI patients have stronger Tregs-related immunosuppression status compared with probable AD dementia patients.